'Self-screening' for malnutrition with an electronic version of the Malnutrition Universal Screening Tool ('MUST') in hospital outpatients: concurrent validity, preference and ease of use. Issue 5 (30th July 2018) - Cawood, Abbie L.; Walters, Emily R.; Sharp, Sarah K. E.; Elia, Marinos; Stratton, Rebecca J.
Abstract: Self-screening using an electronic version of the Malnutrition Universal Screening Tool ('MUST') has been developed but its implementation requires investigation. A total of 100 outpatients (mean age 50 (sd 16) years; 57 % male) self-screened with an electronic version of 'MUST' and were then screened by a healthcare professional (HCP) to assess concurrent validity. Ease of use, time to self-screen and prevalence of malnutrition were also assessed. A further twenty outpatients (mean age 54 (sd 15) years; 55 % male) examined preference between self- screening with paper and electronic versions of 'MUST'. For the three-category classification of 'MUST' (low, medium and high risk), agreement between electronic self-screening and HCP screening was 94 % ( κ =0·74, se 0·092; P <0·001). For the two-category classification (low risk; medium+high risk) agreement was 96 % ( κ =0·82, se 0·085; P <0·001), comparable with the previously reported paper-based self-screening. In all, 15 % of patients categorised themselves 'at risk' of malnutrition (5 % medium, 10 % high). Electronic self-screening took 3 min (sd 1·2 min), 40 % faster than previously reported for the paper-based version. Patients found the tool easy or very easy to understand (99 %) and complete (98 %). Patients that assessed both tools found the electronic tool easier to complete (65 %) and preferred it (55 %) to the paper version. Electronic self-screening using 'MUST' in a heterogeneous group of hospital outpatients is acceptable, user-friendly and has 'substantial to almost-perfect' agreement with HCP screening. The electronic format appears to be as agreeable and often the preferred format when compared with the validated paper-based 'MUST' self-screening tool.